âSapituduhiraâ Visualizing the Myth of Animals in Popular Javanese Beliefs with Woodcut Technique - Fajar Astrianto, Muhammad
"Sapituduhira" is the theme title of this work which is adapted from Javanese poem, which means advice or guidance. The term is found in poem titled Pocung which in Javanese society is a poem usually used to convey advice and contains various human teachings in order to be able to bring themselves to navigate life in harmony both physically and mentally. The Javanese believe that God is the center of the universe and the center of all life. Before everything happened in the world, God already existed. Kawula lan Gusti, is a Javanese term that is at the core of the views and life guidelines for Javanese people. The view assumes that the moral obligation of man is to achieve harmony with the last force and in the last unity that man totally surrenders himself as a servant to his Gusti (the Creator). The scholarships are conveyed through artifacts of traditional art and through the diachronic or oral system from generation to generation. One of them is advice about good or bad things that are often passed down through the family. The advices were also experienced by the author in his life through stories of myths revealed in the family. Some of these are remembered in the author’s memory, namely the myth about animals. Animal mythical stories that are experienced directly by the writer or just by knowing the story finally inspires to make art work. The author wants to visualize the Javanese popular myths, especially myths about animals, through contemporary artworks made using woodcut techniques - a traditional and conventional printmaking method, with color compositions that refer to popular culture as the response of the writer as a modern society to the culture.